PENGARUH KUALITAS LAYANAN JUGA KINERJA CUSTOMER SERVICE TERHADAP KEPUASAN NASABAH DI BSI KCP MALANG LAWANG - Iqbal Burhanuddin Maulidy; Afifudin Afifudin; Arista Fauzi Kartika Sari (El-Aswaq, 2022)
The aim of this research is to know the influence of the Service and Performance Quality of Customer Service toward Customer's Satisfaction in Indonesia Islamic Bank KCP Malang Lawang. This research used a quantitative correlational approach. The sampling in this research used the Slovin formula with 94 respondents. The data consist of primary one which is taken from a questionnaire and processed with SPSS 14.0 version. The data analysis used multiple linear regression analysis. The result of this research showed that the Service Quality variable (X1) gave a positive and significant influence toward Customer's Satisfaction (Y), the Service Customer Performance variable (X2) gave a positive and significant influence toward Customer's Satisfaction (Y).